Unveiling Messapic Funerary Discourse - Mani, Kujtim (Respectus Philologicus, 2024)
Messapic, an ancient language from the 6th to the 2nd century BC in Southern Italy, remains a linguistically enigmatic and poorly understood entity, has been traditionally classified as an extinct language. Current scholarship predominantly views Messapic epigraphy as primarily consisting of personal names, anthroponyms, and theonyms. However, attempts to linguistically classify and interpret it within the broader framework of Greek, Latin, or other ancient languages have yielded limited insights. This article investigates Messapic epigraphy as a potential descendant of Proto-Albanian and reveals intriguing parallels with classical Albanian. The chosen exemplars challenge the prevailing assumption that Messapic is an extinct language, presenting it in a new light and underscoring its enduring linguistic and cultural legacy. This is notably exemplified through a distinctive funerary discourse that serves as a hallmark of the Messapic language.